Glutamate in Pyridoxine-Dependent Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
Cerebrospinal fluid levels of glutamate, g-aminobutyric acid, and pyridoxal-5-phosphate examined in a patient with pyridoxine dependency while on and off vitamin B6 treatment are reported from Universitat Munchen, and Universitats-Nervenklinik, Wurzburg, Germany.